Panama : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
This 2004 Article IV Consultation for Panama reports that the medium-term outlook is encouraging, assuming implementation of the authorities' fiscal program, which should put the public debt ratio on a steadily declining path. The banking system experienced a substantial recovery in 2003-04, and the financial system remains essentially sound, with favorable performance indicators and a strong regulatory framework. An expansion of the Panama Canal at an estimated cost of more than 30 percent of GDP could, if approved in a national referendum, have a far-reaching impact on the economy's growth prospects.